Language Style in Sabrina Carpenter’s Interview on the Apple Music Youtube Channel : A sociolinguistic study - Ananta Imelda Saputri Dewi; Dona Rahayu Sugiharti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study investigates the language styles used by Sabrina Carpenter in her interview with Zane Lowe on the Apple Music YouTube channel and examines how those styles reflect her identity. The study applies a descriptive qualitative approach. Sabrina Carpenter’s utterances in the 53-minute-and-5-second interview were transcribed, identified, coded, and classified using William Labov’s (1972) language-style framework, while Janet Holmes’s (2013) sociolinguistic perspective was used to interpret the relationship between language and identity. The findings show 100 relevant data consisting of 92 casual-style utterances and 8 careful-style utterances. Reading style, word-list style, and minimal-pairs style were not found because the interview did not involve controlled reading or elicitation tasks. Casual style was characterized by spontaneous responses, short utterances, interjections, discourse markers, humor, contractions, emotional expressions, and incomplete structures. Careful style appeared when Carpenter gave more deliberate, coherent, reflective, and interactionally managed responses. The dominance of casual style indicates that Carpenter generally communicates in a relaxed and natural manner. Her linguistic choices construct an identity that is relatable, authentic, expressive, friendly, and socially engaging, while careful style additionally presents her as reflective and attentive to interaction. The study demonstrates that language style functions not only as linguistic variation but also as a resource for identity construction in digital media interviews.